An Amplicon Panel for High-Throughput and Low-Cost Genotyping of Yesso Scallop Mizuhopecten yessoensis - Ben J. G. Sutherland; Chen Yin Walker; Denman Moody; Chelsea Bennett; Marissa Wright-LaGreca; Chloe Shamash-McLaughlin; Karen Leask; Daniel Roth; Megan Lebeuf; Timothy J. Green (Marine Biotechnology, 2026)

Fraction-specific pathways of sulfur cycling in agroecosystems with highly weathered soils - Wenxiang Zhou; Brigid A. McKenna; Timothy I. McLaren; Ram C. Dalal; Joshua Bennett-Jones; Peter M. Kopittke (Agriculture, Ecosystems & Environment, 2026)

Thermal tolerance and acclimation limits in bull trout ( Salvelinus confluentus ) alevin - Brendan Maldonado; Travis Durhack; Andrew Chapelsky; Sarah E. Glowa; Analisa Lazaro‐Côté; Raven M. Bennett; Timothy Bartley; Neil J. Mochnacz (Journal of Fish Biology, 2026)
The critical thermal maximum ( CT max ) of bull trout ( Salvelinus confluentus ) alevin was measured after 3 weeks of acclimation to 4–21°C. CT max increased from 24.3 at 4°C to 26.7 at 9°C, plateaued between 9 and 12°C (26.9°C), and declined to 25.9°C at 15°C. Acclimation mortality increased above 12°C, reaching 53.7% at 15°C, and no fish survived at 18–21°C. Condition factor declined at ≥12°C. Results indicate bull trout alevin have limited acclimation capacity beyond 12°C and suggest high vulnerability to lethal stress in streams where temperatures exceed this threshold.

Novel symbioses between reef fishes and serpulid polychaetes in the Caribbean Sea - Morgan F. Bennett-Smith; Elizabeth McNamee; Samantha Masih; Timothy Lis; Mason Murchison; Allison Cinelli; Toshith Bhaumik; Catheline Y. M. Froehlich; Anna DeLoach; Ned DeLoach; Ninon Martinez; Peter M. Buston; et al. (Symbiosis, 2026)

Shallow seasonal stratification ameliorates coral bleaching during record-breaking marine heatwaves in a marginal subtropical system - Gonzalo Pérez-Rosales; Yu-De Pei; Joshua Bennett-Williams; Timothy B. King; Markus Rummel; Tzu Hao Chung; Alex S. J. Wyatt (Coral Reefs, 2026)
Marine heatwaves are intensifying globally, with the Fourth Global Coral Bleaching Event (GCBE) beginning in 2023, yet coral bleaching outcomes remain highly variable across space and time. This study examines the role of fine-scale thermal variation in shaping bleaching impacts during two record-breaking marine heatwaves (2022 and 2024) affecting shallow coral assemblages in the marginal and urbanised environments of Hong Kong. Using high-resolution in situ temperature loggers, we quantified thermal exposure across coral-inhabited depths (1–8 m) at three sites and related this to bleaching prevalence across taxa. In 2024, surface temperatures exceeded the local bleaching threshold (29.7 °C) for 37 days, resulting in heat accumulation that reached 25.2 °C days (9.24 °C weeks) and remained above 8 °C days (°C weeks) for 46 days (20 days). However, seasonal stratification created vertical gradients of up to 9.6 °C between 2 and 8 m, reducing the magnitude and duration of heat accumulation severalfold (e.g., up to 35.4 °C days and 76 days > 8 °C days at 2 m, compared to 7.9 °C days at 8 m). Bleaching prevalence was 20–46% lower between 1 and 5 m, with Bayesian bleaching probabilities highest for Goniopora (82%) and lowest for Porites (64%). These patterns could not be explained by satellite-derived sea surface temperatures alone. Despite record heating and stress, mortality was limited (60 to 95% pigmentation recovery). Our findings provide rare fine-scale assessments of bleaching and thermal dynamics, including during the Fourth GCBE, and highlight how local stratification can create thermal refuges. Understanding how oceanographic contexts structure these refuges is essential for identifying and conserving coral communities with greater survival potential under accelerating ocean heating.

Functional group composition of soil organic carbon varies between soil organic matter fractions but not with long-term cropping or soil depth - Wenxiang ZHOU; Brigid A. MCKENNA; Joshua BENNETT-JONES; Timothy I. MCLAREN; Ram C. DALAL; Peter M. KOPITTKE (Pedosphere, 2025)

New records of fishes from the Coral Sea Marine Park, Australia - Yi-Kai Tea; Tiffany L. Sih; Fenton Walsh; Timothy Bennett; Luiz A. Rocha; Ghislain Bardout; Amanda Hay; Kerryn Parkinson; Sally Reader; Indiana J. Riley; John J. Pogonoski; Jeffrey W. Johnson; et al. (Coral Reefs, 2025)
With an area covering just under 1 million km 2 , Australia’s Coral Sea Marine Park (CSMP) is among the largest marine protected areas globally. Yet, the demersal deep-reef fish fauna of the CSMP remains poorly described, due in part to its remote location, as well as its sheer size, much of which is inaccessible below conventional SCUBA diving depths. Recent remotely operated vehicle (ROV) explorations conducted by the Schmidt Ocean Institute provided an opportunity to explore the benthic ichthyofauna of deep mesophotic and rariphotic coral ecosystems. Contributions to the deep, demersal ichthyofauna of Australia’s CSMP are herein supplemented with an integrative dataset consisting of ROV imagery and specimen vouchers. Sixty-two new records of fishes from 26 families are reported from the CSMP. Of these, 45 are new Australian records, one of which is also a new family record for Australia. Four species are new records for the Southern Hemisphere, and 21 species are potentially new to science. We report new voucher material for 29 species, including several species previously identified as new for the CSMP with no voucher specimens.

Metabolic Insights Into Microbially Induced Calcite Formation by Bacillaceae for Application in Bio‐Based Construction Materials - Michael Seidel; Charlotte Hamley‐Bennett; Bianca J. Reeksting; Manpreet Bagga; Lukas Hellmann; Timothy D. Hoffmann; Christiane Kraemer; Irina Dana Ofiţeru; Kevin Paine; Susanne Gebhard (Environmental Microbiology, 2025)
Microbially induced calcite precipitation (MICP) offers promising solutions for sustainable, low‐cement infrastructure materials. While it is known how urea catabolism leads to biomineralisation, the non‐ureolytic pathways of MICP are less clear. This limits the use of the latter in biotechnology, despite its clear benefit of avoiding toxic ammonia release. To address this knowledge gap, the present study explored the interdependence between carbon source utilisation and non‐ureolytic MICP. We show that acetate can serve as the carbon source driving calcite formation in several environmental Bacillaceae isolates. This effect was particularly clear in a Solibacillus silvestris strain, which could precipitate almost all provided calcium when provided with a 2:1 acetate‐to‐calcium molar ratio, and we show that this process was independent of active cell growth. Genome sequencing and gene expression analyses revealed an apparent link between acetate catabolism and calcite precipitation in this species, suggesting MICP may be a calcium stress response. Development of a simple genetic system for S. silvestris led to the deletion of a proposed calcium binding protein, although this showed minimal effects on MICP. Taken together, this study provides insights into the physiological processes leading to non‐ureolytic MICP, paving the way for targeted optimisation of biomineralisation for sustainable materials development.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Knowledge co-production for identifying indicators and prioritising solutions for food and land system sustainability in Australia - Romy L. Zyngier; Carla L. Archibald; Brett A. Bryan; Haley Lambert; Enayat A. Moallemi; Mark Elliott; Mark Lawrence; Jane Hutchinson; Lauren T. Bennett; Timothy Reeves; Matthew Pryor; Ulrika Lindholm; et al. (Sustainability Science, 2024)
Achieving sustainable Australian food and land systems requires the rapid implementation and scaling up of a broad suite of solutions to meet the Sustainable Development Goals (SDGs). Decision-making frameworks are needed to identify suitable indicators and prioritise solutions at national scales to inform sustainability transitions. Using a knowledge co-production framework, we convened 150 stakeholders from 100 + organisations to identify 18 nationally relevant indicators that aligned with critical SDGs describing a sustainable food and land system for Australia, in addition to 78 key solutions (supply- and demand-side) to enable progress against these indicators. We then asked subject matter experts to code the impact of each solution on each indicator using an adapted interaction mapping method accounting for uncertainty. The solution category ‘Protecting and restoring nature’, which included solutions targeting conservation and restoration, showed the highest potential for capturing synergies and avoiding trade-offs across multiple indicators. This category exhibited 34.6% of total major synergies, supporting the achievement of clean water and sanitation (SDG6), economic growth (SDG12), life under water (SDG14), and life on land (SDG15). The solution category ‘Carbon sequestration’, which included technological and biological carbon dioxide removal solutions, had the highest number of trade-offs with individual sustainability indicators (42.3%), particularly those relating to zero hunger (SDG2), wellbeing (SDG3), SDG6, SDG14, and SDG15. Our framework can be used to inform future research investment, support the prioritisation of solutions for quantitative modelling, and inform discussions with stakeholders and policymakers for transforming national-scale food and land systems in alignment with the SDGs.

DeepN4: Learning N4ITK Bias Field Correction for T1-weighted Images - Praitayini Kanakaraj; Tianyuan Yao; Leon Y. Cai; Ho Hin Lee; Nancy R. Newlin; Michael E. Kim; Chenyu Gao; Kimberly R. Pechman; Derek Archer; Timothy Hohman; Angela Jefferson; Lori L. Beason-Held; et al. (Neuroinformatics, 2024)

Unconfined fishway design, implementation, and assessment for the emerald Shiner (Notropis atherinoides) in the Upper Niagara River, New York - Jundong Qiao; Sean J. Bennett; Joseph F. Atkinson; Paul A. Cocca; Sarah K. Delavan; Andrew R. Hannes; Bryan A. Hinterberger; Timothy J. Pede; Alicia Pérez-Fuentetaja; Richard J. Ruby (Ecological Engineering, 2024)

Browsing by non-native invasive sambar deer dramatically impacts forest structure - Timothy J. Wills; Richard W.R. Retallick; Joe Greet; Ami Bennett (Forest Ecology and Management, 2023)

Complex crop rotations improve organic nitrogen cycling - Lauren C. Breza; Maria Mooshammer; Timothy M. Bowles; Virginia L. Jin; Marty R. Schmer; Bennett Thompson; A. Stuart Grandy (Soil Biology and Biochemistry, 2023)

Historic palaeobotanical collection reveals in situ microspores and pollen from Early Carboniferous (Tournaisian) ovules from the Ballagan Formation of Scotland - Emma Reeves; John E.A. Marshall; Carys Bennett; Sarah Davies; Timothy Kearsey; David Millward (Review of Palaeobotany and Palynology, 2023)

Infection‐competent monkeypox virus contamination identified in domestic settings following an imported case of monkeypox into the UK - Barry Atkinson; Christopher Burton; Thomas Pottage; Katy‐Anne Thompson; Didier Ngabo; Ant Crook; James Pitman; Sian Summers; Kuiama Lewandowski; Jenna Furneaux; Katherine Davies; Timothy Brooks; et al. (Environmental Microbiology, 2022)
An imported case of monkeypox was diagnosed in December 2019 in a traveller returning from Nigeria to the UK. Subsequently, environmental sampling was performed at two adjoining single‐room residences occupied by the patient and their sibling. Monkeypox virus DNA was identified in multiple locations throughout both properties, and monkeypox virus was isolated from several samples 3 days after the patient was last in these locations. Positive samples were identified following the use of both vacuum and surface sampling techniques; these methodologies allowed for environmental analysis of potentially contaminated porous and non‐porous surfaces via real‐time quantitative reverse transcriptase PCR analysis in addition to viral isolation to confirm the presence of infection‐competent virus. This report confirms the potential for infection‐competent monkeypox virus to be recovered in environmental settings associated with known positive cases and the necessity for rapid environmental assessment to reduce potential exposure to close contacts and the general public. The methods adopted in this investigation may be used for future confirmed cases of monkeypox in order to establish levels of contamination, confirm the presence of infection‐competent material and to identify locations requiring additional cleaning.

Aging and white matter microstructure and macrostructure: a longitudinal multi-site diffusion MRI study of 1218 participants - Kurt G. Schilling; Derek Archer; Fang-Cheng Yeh; Francois Rheault; Leon Y. Cai; Colin Hansen; Qi Yang; Karthik Ramdass; Andrea T. Shafer; Susan M. Resnick; Kimberly R. Pechman; Katherine A. Gifford; et al. (Brain Structure and Function, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Thermal optima of gross primary productivity are closely aligned with mean air temperatures across Australian wooded ecosystems - Alison C. Bennett; Stefan K. Arndt; Lauren T. Bennett; Jürgen Knauer; Jason Beringer; Anne Griebel; Nina Hinko‐Najera; Michael J. Liddell; Daniel Metzen; Elise Pendall; Richard P. Silberstein; Timothy J. Wardlaw; et al. (Global Change Biology, 2021)
Gross primary productivity (GPP) of wooded ecosystems (forests and savannas) is central to the global carbon cycle, comprising 67%–75% of total global terrestrial GPP. Climate change may alter this flux by increasing the frequency of temperatures beyond the thermal optimum of GPP ( T opt ). We examined the relationship between GPP and air temperature (Ta) in 17 wooded ecosystems dominated by a single plant functional type (broadleaf evergreen trees) occurring over a broad climatic gradient encompassing five ecoregions across Australia ranging from tropical in the north to Mediterranean and temperate in the south. We applied a novel boundary‐line analysis to eddy covariance flux observations to (a) derive ecosystem GPP–Ta relationships and T opt (including seasonal analyses for five tropical savannas); (b) quantitatively and qualitatively assess GPP–Ta relationships within and among ecoregions; (c) examine the relationship between T opt and mean daytime air temperature (MDTa) across all ecosystems; and (d) examine how down‐welling short‐wave radiation (Fsd) and vapour pressure deficit (VPD) influence the GPP–Ta relationship. GPP–Ta relationships were convex parabolas with narrow curves in tropical forests, tropical savannas (wet season), and temperate forests, and wider curves in temperate woodlands, Mediterranean woodlands, and tropical savannas (dry season). Ecosystem T opt ranged from 15℃ (temperate forest) to 32℃ (tropical savanna—wet and dry seasons). The shape of GPP–Ta curves was largely determined by daytime Ta range, MDTa, and maximum GPP with the upslope influenced by Fsd and the downslope influenced by VPD. Across all ecosystems, there was a strong positive linear relationship between T opt and MDTa (Adjusted R 2 : 0.81; Slope: 1.08) with T opt exceeding MDTa by >1℃ at all but two sites. We conclude that ecosystem GPP has adjusted to local MDTa within Australian broadleaf evergreen forests and that GPP is buffered against small Ta increases in the majority of these ecosystems.

Lower cardiac output is associated with neurodegeneration among older adults with normal cognition but not mild cognitive impairment - Elizabeth E. Moore; Dandan Liu; Corey W. Bown; Hailey A. Kresge; Deepak K. Gupta; Kimberly R. Pechman; Lisa A. Mendes; L. Taylor Davis; Katherine A. Gifford; Adam W. Anderson; Thomas J. Wang; Bennett A. Landman; et al. (Brain Imaging and Behavior, 2021)

Homogenization of freshwater lakes: Recent compositional shifts in fish communities are explained by gamefish movement and not climate change - Kevin Cazelles; Timothy Bartley; Matthew M. Guzzo; Marie‐Hélène Brice; Andrew S. MacDougall; Joseph R. Bennett; Ellen H. Esch; Taku Kadoya; Jocelyn Kelly; Shin‐ichiro Matsuzaki; Karin A. Nilsson; Kevin S. McCann (Global Change Biology, 2019)
Globally, lake fish communities are being subjected to a range of scale‐dependent anthropogenic pressures, from climate change to eutrophication, and from overexploitation to species introductions. As a consequence, the composition of these communities is being reshuffled, in most cases leading to a surge in taxonomic similarity at the regional scale termed homogenization. The drivers of homogenization remain unclear, which may be a reflection of interactions between various environmental changes. In this study, we investigate two potential drivers of the recent changes in the composition of freshwater fish communities: recreational fishing and climate change. Our results, derived from 524 lakes of Ontario, Canada sampled in two periods (1965–1982 and 2008–2012), demonstrate that the main contributors to homogenization are the dispersal of gamefish species, most of which are large predators. Alternative explanations relating to lake habitat (e.g., area, phosphorus) or variations in climate have limited explanatory power. Our analysis suggests that human‐assisted migration is the primary driver of the observed compositional shifts, homogenizing freshwater fish community among Ontario lakes and generating food webs dominated by gamefish species.

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Distributional responses to marine heat waves: insights from length frequencies across the geographic range of the endemic reef fish Choerodon rubescens - Katherine Cure; Jean-Paul A. Hobbs; Timothy J. Langlois; David A. Abdo; Scott Bennett; Euan S. Harvey (Marine Biology, 2018)

Reconstructing overfishing: Moving beyond Malthus for effective and equitable solutions - Elena M Finkbeiner; Nathan J Bennett; Timothy H Frawley; Julia G Mason; Dana K Briscoe; Cassandra M Brooks; Crystal A Ng; Rosana Ourens; Katherine Seto; Shannon Switzer Swanson; Jose Urteaga; Larry B Crowder (Fish and Fisheries, 2017)
Inaccurate or incomplete diagnosis of the root causes of overfishing can lead to misguided and ineffective fisheries policies and programmes. The “Malthusian overfishing narrative” suggests that overfishing is driven by too many fishers chasing too few fish and that fishing effort grows proportionately to human population growth, requiring policy interventions that reduce fisher access, the number of fishers, or the human population. By neglecting other drivers of overfishing that may be more directly related to fishing pressure and provide more tangible policy levers for achieving fisheries sustainability, Malthusian overfishing relegates blame to regions of the world with high population growth rates, while consumers, corporations and political systems responsible for these other mediating drivers remain unexamined. While social–ecological systems literature has provided alternatives to the Malthusian paradigm, its focus on institutions and organized social units often fails to address fundamental issues of power and politics that have inhibited the design and implementation of effective fisheries policy. Here, we apply a political ecology lens to unpack Malthusian overfishing and, relying upon insights derived from the social sciences, reconstruct the narrative incorporating four exemplar mediating drivers: technology and innovation, resource demand and distribution, marginalization and equity, and governance and management. We argue that a more nuanced understanding of such factors will lead to effective and equitable fisheries policies and programmes, by identifying a suite of policy levers designed to address the root causes of overfishing in diverse contexts.

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Mapping marine debris across coastal communities in Belize: developing a baseline for understanding the distribution of litter on beaches using geographic information systems - Paulita Bennett-Martin; Christy C. Visaggi; Timothy L. Hawthorne (Environmental Monitoring and Assessment, 2016)

GSK3β Interactions with Amyloid Genes: An Autopsy Verification and Extension - Timothy J. Hohman; Lori Chibnik; William S. Bush; Angela L. Jefferson; Phillip L. De Jaeger; Tricia A. Thornton-Wells; David A. Bennett; Julie A. Schneider (Neurotoxicity Research, 2015)

Relationships between stream phosphorus concentrations and drainage basin characteristics in a watershed with poultry farming - Timothy J. Cox; Bernard A. Engel; Roger L. Olsen; J. B. Fisher; Andrew D. Santini; Brian J. Bennett (Nutrient Cycling in Agroecosystems, 2013)

The role of platelet CD154 in the modulation in adaptive immunity - Daniel L. Sprague; Jennifer M. Sowa; Bennett D. Elzey; Timothy L. Ratliff (Immunologic Research, 2007)

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

Association of bovine neonatal Fc receptor a-chain gene (FCGRT) haplotypes with serum IgG concentration in newborn calves - William W. Laegreid; Michael P. Heaton; James E. Keen; William M. Grosse; Carol G. Chitko-McKown; Timothy P.L. Smith; John W. Keele; Gary L. Bennett; Thomas E. Besser (Mammalian Genome, 2002)

Selection and use of SNP markers for animal identification and paternity analysis in U.S. beef cattle - Michael P. Heaton; Gregory P. Harhay; Gary L. Bennett; Roger T. Stone; W. Michael Grosse; Eduardo Casas; John W. Keele; Timothy P.L. Smith; Carol G. Chitko-McKown; William W. Laegreid (Mammalian Genome, 2002)

Use of bovine EST data and human genomic sequences to map 100 gene-specific bovine markers - Roger T. Stone; W. Michael Grosse; Eduardo Casas; Timothy P.L. Smith; John W. Keele; Gary L. Bennett (Mammalian Genome, 2002)

Comparative mapping of BTA15 and HSA11 including a region containing a QTL for meat tenderness - Caird E. Rexroad III; Gary L. Bennett; Roger T. Stone; John W. Keele; Scott C. Fahrenkrug; Brad A. Freking; Steven M. Kappes; Timothy P.L. Smith (Mammalian Genome, 2001)

Land-Use Dynamics in a Southern Illinois (USA) Watershed - CHRISTOPHER LANT; TIMOTHY LOFTUS; STEVEN KRAFT; DAVID BENNETT (Environmental Management, 2001)